Legal Ethics of Sustainable Environmental Management - PRASETYO, Yogi; INDIANTONESIAORO, Alfalachu; ISNANDAR, Aries (Indonesia Strategic Sustainability, 2025)
Environmental potential which is quite large economically has been misused to obtain the maximum profit. This can be seen from the many cases of law violations in the environmental sector and physical evidence of environmental damage due to wrongful exploitation. Certain interests that come into play in environmental management have damaged the environmental law management system itself. Law is only used as a tool to control natural resources legally. Many state officials cooperate with unscrupulous businessmen to exploit the environment freely without paying attention to the boundaries that are the size that should be the reference. In Indonesia environmental problems are important and urgent to be addressed by finding solutions to solve them. Therefore environmental management laws must always be accompanied by civilized Indonesian human attitudes, namely an attitude that shows the quality of Indonesian humanity which is based on religion, culture and science. So that on this basis the environment can be managed properly, not only for business benefits, but also for the welfare of society and for the benefit of the universe.